2020
DOI: 10.3390/jcm9010135
|View full text |Cite
|
Sign up to set email alerts
|

Male Predominance of Gastric Cancer among Patients with Hypothyroidism from a Defined Geographic Area

Abstract: In the past, hypothyroidism has been associated with an increased susceptibility to gastric cancer (GC). Although several epidemiological studies have corroborated this association, a precise mechanistic explanation remains elusive. In this study, this hypothesis was tested by using a large database of subjects who underwent upper endoscopy for various reasons. This was a retrospective, case-control, single-center study. Subjects with GC (cases) were compared with subjects without (controls), according to hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Interestingly, in the present study the strong association of GC with goiter was significant only in males, in line with our recent clinical observation (Dore et al, 2020) reinforcing the hypothesis that the association is likely sex-dependent and involves different mechanisms in men and women. The fact that the hotspot of GC mortality mainly affects men is intriguing and deserves further studies.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, in the present study the strong association of GC with goiter was significant only in males, in line with our recent clinical observation (Dore et al, 2020) reinforcing the hypothesis that the association is likely sex-dependent and involves different mechanisms in men and women. The fact that the hotspot of GC mortality mainly affects men is intriguing and deserves further studies.…”
Section: Discussionsupporting
confidence: 93%
“…It has previously been reported that shepherds are frequently positive for H. pylori infection (e.g., 98%), and the sheep's stomach may be a reservoir of the bacteria Dore et al, 2001). However, in the present study, the strength of association with GC was statistically higher for goiter, similarly to our previous observation (Dore et al, 2020).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Here, the patient had a history of hypothyroidism related to anti-TG and anti-TPO antibodies and gastrectomy by gastric cancer. Classically, hypothyroidism has been reported to be associated with an increased susceptibility to gastric cancer [5]. Gastrectomy is a risk factor for thiamine deficiency, which could occur within four to six weeks postoperatively [6,7].…”
Section: Discussionmentioning
confidence: 99%